2017
DOI: 10.1016/j.jcp.2017.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis on chaotic dynamical systems by Non-Intrusive Least Squares Shadowing (NILSS)

Abstract: This paper develops the Non-Intrusive Least Squares Shadowing (NILSS) method, which computes the sensitivity for long-time averaged objectives in chaotic dynamical systems. In NILSS, we represent a tangent solution by a linear combination of one inhomogeneous tangent solution and several homogeneous tangent solutions. Next, we solve a least squares problem using this representation; thus, the resulting solution can be used for computing sensitivities. NILSS is easy to implement with existing solvers. In additi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
127
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(127 citation statements)
references
References 40 publications
0
127
0
Order By: Relevance
“…-Secondly, another avenue would be to adapt the very effective techniques based on the Covariant Lyapunov vectors (CLVs) to non-stationary dynamics. These techniques were recently introduced (Wang, 2013;Ni and Wang, 2017;Ni, 2019) to deal with stationary responses of chaotic systems, i.e. the response of a system that lies on its attractor.…”
Section: Discussionmentioning
confidence: 99%
“…-Secondly, another avenue would be to adapt the very effective techniques based on the Covariant Lyapunov vectors (CLVs) to non-stationary dynamics. These techniques were recently introduced (Wang, 2013;Ni and Wang, 2017;Ni, 2019) to deal with stationary responses of chaotic systems, i.e. the response of a system that lies on its attractor.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the cost of the two main adjoint-based sensitivity methods in the literature, namely the Least Squares Shadowing (LSS) 26 and the Ensemble Adjoint (EA) methods, increases with the number and/or magnitude of positive Lyapunov exponents in the discrete system. The computational cost of shadowing-based approaches, including the original LSS method, the Multiple Shooting Shadowing (MSS) method 2 and the Non-Intrusive LSS (NILSS) method, 3,17 is proportional to the number of positive Lyapunov exponents. Under optimistic assumptions, including uniform hyperbolicity and exponential decay of correlations, Chandramoorthy et al 5,6 showed that the mean squared error in the EA estimator is a power law of the computational cost, where the power constant depends on the leading exponent.…”
Section: Application To Chaotic Adjointsmentioning
confidence: 99%
“…Second, conventional sensitivity analysis methods break down for chaotic systems; 14 which compromises critical tasks in engineering such as flow control, design optimization, error estimation, data assimilation, and uncertainty quantification. While a number of sensitivity analysis methods have been proposed for chaotic systems, including Fokker-Planck methods, 23 FluctuationDissipation methods, 15 the Ensemble Adjoint (EA) method, 14 the Least Squares Shadowing (LSS) method 26 and the Non-Intrusive Least Squares Shadowing (NILSS) method, 17 they all come at a high computational cost. This is ultimately related to the positive portion of the Lyapunov spectrum of the system, and the cost of each method is sensitive to different aspects of it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional tangent/adjoint approaches cannot be used to compute sensitivities of statistical averages (or long-time averaged quantities) in these high-fidelity, eddy-resolving simulations. This is because the tangent and adjoint solutions diverge exponentially [13,14], since these simulations exhibit chaotic behavior i.e., infinitesimal perturbations to initial conditions grow exponentially in time. For this reason, sensitivity studies on DNS or LES have been restricted to short-time horizons; these short-time sensitivities have found limited applicability including in flow control in combustion systems [15], jet noise reduction [5] and structural design [16].…”
Section: Introductionmentioning
confidence: 99%